Problem-solving with industrial drawings: Supporting formal graphics language development for Malaysian engineering graduates - Burvill, Colin; Field, Bruce; Abdullah, Zulkeflee; Alias, Maizam (Tempus Publications, 2016)
The globalisation of manufacture has forced many developing countries in Asia to respond to the exacting requirements of quality and interchangeability that involve complex and diverse conventions for graphical and geometrical product specifications. Competing pressure for international recognition of engineering qualifications has reduced the time available in Malaysian universities to teach a range of practical skills, including those of reading and interpreting engineering drawings (RIED), although Malaysian industry has identified inadequacies in the RIED skills of recent graduates. This paper reports the deliberate use of incidental learning to increase RIED skills in groups of undergraduate engineering students byreplacing the familiar line illustrations of parts and machines in the learning tasks ofa conventional analytical subject with sets of formal engineering drawings. Participants who were engaged for 14 hours of practical problem solving work in the subject and a parallel CAD-modelling subject, gained measurable skills in RIED. Since the increase in participants' RIED skill did not require alterations to the existing educational objectives of the subjects, the time allocated to problem-solving within those subjects or additional RIED teaching expertise, an expansion of the approach is recommended.